Development of the Heidelberg Airborne Imaging DOAS Instrument (HAIDI) - A novel remote sensing device for the investigation of two- and three-dimensional trace gas distributions in the troposphere - General, Stephan (2014)
The investigation of trace gases and related chemical processes in the atmosphere on local and regional scales requires measurement techniques with high spatial resolution and coverage. In the context of this thesis a novel remote sensing device, the Heidelberg Airborne Imaging DOAS Instrument (HAIDI), was developed. HAIDI works on the basis of the well established DOAS method and has the ability to determine horizontal and vertical distributions of several important atmospheric species with a resolution of better than 100 m at high sensitivity. The thesis gives a detailed overview on the operating principle of the instrument and its characteristics. In addition, measurement results of several field campaigns with this instrument are presented, which yielded interesting findings. For instance, BrO/SO2 ratios were measured at Mt. Etna (Italy), showing constant values of 1.4 × 10−4 and 2.0 × 10−4, respectively, along the plume’s centerline on both measurement days (observed plume ages: 2–34 min), but an increase by a factor of two to three towards the edges of the plume. Moreover, a temporal change in the BrO/SO2 ratio was observed prior to the culmination of a paroxysm. The measurements are also one of the first to show spatial resolved OClO/SO2 and OClO/BrO ratios in the plume of Mt. Etna. Further measurements were performed near Indianapolis (Indiana, USA) and Barrow (Alaska, USA) to investigate the spatial distribution of NO2 over polluted urban areas as well as the occurrence of “bromine explosion” events during boundary layer ozone depletion in polar regions. The data allow to characterize the spatial distribution of BrO and thus give insight into possible bromine sources.